Effect of Sweet potato (Ipomoea batatas (L.) Lam) leaf extract on hypoglycaemia, blood insulin secretion, and key carbohydrate metabolic enzymes in expermentally obese and STZ-induced diabetic mice - Lien, Do Ngoc; Phuc, Do Van; Lien, Pham Quynh; Trang, Ngo Thi; Kien, Tran Trung; Lien, Tran Thi Phuong; Tien, Kim Dinh (VNU Journal of Science: Natural Sciences and Technology, 2011)
Abstract. Hypolipidemic, hypoglycaemic effects of the ethyl acetate extract fraction from leaves of sweet potato ( Ipomoea batatas (L) Lam.) (Convonvulaceae) in obese and streptozotocin (STZ) induced type 2 diabetic mice were demonstrated. When obese-diabetic mice was administrated orally daily by ethyl acetate fraction of  1000mg lyophilized powder/kg for 21 days, we showed that maximum hypoglycaemic(36.77%) and hypolipidemic effects, such as TC(35.18%), TG(29.17%), and LDLc(51.97%) were proven in treated mice compared to the control (untreated mice). The hypoglycaemic effects of ethyl acetate extract fraction from leaves of sweet potato so that it accelerated hexokinase activity, stimulated  insulin secretion and inhibited gluconeogenesis enzymatic activity (glucose-6-phosphatase). Keywords: Ipomoea batatas leaf, obese mice, type 2 Diabetes mellitus, hypolipidemic and hypoglycaemic effect.